Pengaruh Ekstrak Buah Jambu Biji Merah terhadap Kerusakan Struktur Histologis Hepar Mencit yang Diinduksi Asetaminofen - Vasa Adi Wisnu Wardana; Suyatmi .; Bambang Sukilarso Sakiman (Nexus Biomedika, 2012)
Background: Antioxidants in guava fruit are vitamin C, flavanoid, and lycopene which are estimated having hepato-protective function. The objectives of this research are to know the effect of guava fruit extract and in various doses on mice liver damage induced by acetaminophen. Methods: Samples of 28 male mice, Swiss webster type, 2-3 months old age and + 20gr of each weight, were divided into 4 groups of 7 mice. Guava fruit extract was given for 14 days in a row, while acetaminophen in toxic dose was given on the 12th, 13th, and 14th day. The score of hepatocyte damage was determined by pyknosis, karyorhexis, and karyolysis. The data was analized by One-Way ANOVA test (?= 0,05) and continued by Post Hoc Multiple Comparisons using Least Significant Differences(LSD) test(?= 0,05). Results:The group with the highest average damage of hepatocyte is KP1(84,233,207), and the groups with decrease average damage of hepatocyte are KP2 (48,762,964) and KP3(35,232,755). The results of One-Way ANOVA test showed a significant difference in all group (p<0.001). The statistical data result showed a significant difference of hepatic damage between K-P1, K-KP2, K-KP3, KP1-KP2, KP1-KP3, and KP2-KP3. Conclusion: Guava fruit extract can decrease the histological damage of the hepatocyte of mice induced by acetaminophen. The higher dose of guava fruit extract, the higher protection effect againts liver histological damage from acetaminophen toxic on mice. Key words: guava fruit extract, acetaminophen, histological damage, hepatocyte.